PENGARUH DIFERENSIASI TERHADAP LOYALITAS PELANGGAN DIMANA KEPUASAN PELANGGAN SEBAGAI INTERVENING VARIABEL - Firdaus Firdaus; Ade Octavia (DIGEST MARKETING, 2018)
The purpose of this research is to describe the influence of differentiation on customer loyalty, where customer satisfaction treated as intervening variable. Data was analyzed by structural equation modeling (based on components partial least squares path modeling (PLS-SEM). The results showed that differentiation and customer satisfaction directly affect significantly customer loyalty, and satisfaction. Then customers satisfaction mediate indirectly differentiations and customer loyalty. Hence it is proved that Alfamart has to create customer satisfaction and reached the higher level of loyalty besides resting on the differentiation prices and location. Additionally differentiation is the core of Alfamart should be developed creatively to make them be positioned as modern retailer.